Who is willing to take the risk? Assessing the readiness for living liver donation in the general German population. Issue 7 (30th June 2006) - Popp, F C; Eggert, N; Hoy, L; Lang, S A; Obed, A; Piso, P; Schlitt, H J; Dahlke, M H
Abstract : Background: Shortage of donor organs is one of the major problems for liver transplant programmes. Living liver donation is a possible alternative, which could increase the amount of donor organs available in the short term. Objective: To assess the attitude towards living organ donation in the general population to have an overview of the overall attitude within Germany. Methods: A representative quota of people was evaluated by a mail questionnaire (n = 250). This questionnaire had 24 questions assessing the willingness to be a living liver donor for different potential recipients. Factors for and against living liver donation were assessed. Results: Donating a part of the liver was almost as accepted as donating a kidney. The readiness to donate was highest when participants were asked to donate for children. In an urgent life-threatening situation the will to donate was especially high, whereas it was lower in the case of recipient substance misuse. More women than men expressed a higher disposition to donate for their children. Sex, religion, state of health and age of the donor, however, did not influence other questions on the readiness to consider living organ donation. The will for postmortem organ donation positively correlated with the will to be a living organ donor. Conclusions: The motivation in different demographic subgroups to participate in living liver transplantation is described. Differences in donation readiness resulting from the situation of every donor and recipient are thoroughly outlined. The acceptance for a living liver donation was found to be high – and comparable to that of living kidney donation.